EXPERIMENTAL STUDY AND MODELLING OF CO2 INJECTIVITY IMPAIRMENT BY SALT PRECIPITATION AND FINES MIGRATION - MD YUSOF, MUHAMMAD ASLAM (2022)
Re-injection of carbon dioxide (CO2) into saline aquifer is highlighted as an effective technique to permanently secure anthropogenic gas produced from high CO2 gas fields in Malaysia. Unlike typical gas injection for oil recovery, reactive interactions between CO2, brine, and rock minerals during the continuous injection of CO2 would trigger injectivity-related issues due to salt precipitation and fines migration mechanisms initiated in the aquifer. However, the existing models to predict CO2 injectivity change are limited to porosity change by salt precipitation alone, without considering other CO2, brine, and rock parameters. Moreover, there have been limited systematic experimental studies to understand the impact of these parameters on the CO2 injectivity change. This research work explored the application of neural network (NN) and response surface method (RSM) models to predict the CO2 injectivity change resulting from the combination of salt precipitation and fines migration.